Development and Application of Single‐Nucleotide Polymorphism (SNP) Genetic Markers for Conservation Monitoring of Burbot Populations. Issue 3 (2nd April 2019) - Campbell, Matthew R.; Vu, Ninh V.; LaGrange, Amanda P.; Hardy, Ryan S.; Ross, Tyler J.; Narum, Shawn R.
Abstract: The transboundary (Idaho, USA; and British Columbia, Canada) population of Burbot Lota lota native to the Kootenai River basin once provided a popular sport and commercial fishery and has been culturally significant to the Kootenai Tribe of Idaho for millennia. However, the population has experienced significant declines over the last 30 years, due primarily to habitat loss and alteration caused by water storage and diversion. By the late 1990s, the population was considered functionally extinct, with estimates of fewer than 50 Burbot in the wild and little to no recruitment, prompting an ongoing international recovery effort. As part of these recovery efforts, managers have been actively developing a hatchery supplementation program to rebuild the population and support future tribal subsistence harvest and recreational fisheries. Although supplementation breeding programs have the potential to rapidly rebuild depleted natural populations, careful genetic management is critical. To monitor genetic diversity and potential inbreeding in the broodstock and to provide parentage‐based tagging of supplementation offspring, we developed a set ( N = 96) of highly variable single‐nucleotide polymorphism (SNP) genetic markers. The subset of 96 SNP markers was developed from a larger suite of 6, 517 SNPs that were discovered by using restriction site‐associated DNA sequencing. This cost‐efficient technology allows for the rapid discovery of thousands of SNP markers in species that have not been extensively studied previously or for which there are little existing DNA sequence data. We demonstrated high accuracy (>99%) of our SNP set for parentage and individual identification through simulated and empirical tests. The SNP marker set provides a powerful new tool for managing broodstock and for monitoring and genetically tagging Burbot to track the growth, survival, and movement of released individuals.